Pengembangan Variasi Permainan Kebugaran Jasmani Komponen Kekuatan Otot Pada Kelas IV SDN Bareng 1 Berbasis Flipbook - Visco Armadhani; Dudung Ma’ruf Nuris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a variety of physical fitness games focusing on muscle strength using a flipbook for fourth-grade students at Bareng 1 Public Elementary School. The development of this medium was motivated by the lack of game variety in physical education classes, which often leads students to become bored and less active during learning activities. The flipbook medium was chosen because it can present material in an engaging, interactive, and easily accessible way for both students and teachers. This study employed the Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 1 content expert, 1 media expert, and 38 fourth-grade students at Bareng 1 Public Elementary School. Data collection techniques included an expert validation questionnaire and a student response questionnaire. The validation results from the content expert indicated that the product received a “highly valid” rating with a feasibility percentage of 97%, while the validation results from the media expert also received a “highly valid” rating with a percentage of 95%. Furthermore, the implementation results among students were 96.74% and among physical education teachers were 97.46%. Student and physical education teacher responses to the use of the flipbook also indicated a “highly valid” category, as the medium was deemed engaging, easy to use, and helpful in boosting learning motivation during physical fitness activities. Based on the results of this study, it can be concluded that the variety of physical fitness games focusing on muscle strength using flipbooks is suitable for use as a teaching medium in physical education for fourth-grade students at Bareng 1 Public Elementary School.